2011
DOI: 10.1111/j.1095-8649.2011.02951.x
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural responses of hatchery‐reared and wild codGadus morhuato mechano‐acoustic predator signals

Abstract: The behavioural responses of wild (predator-experienced) and hatchery-reared (predator-naive) cod Gadus morhua to standardized mechano-acoustic (MA) stimuli were compared in the laboratory. Wild fish responded mainly with freezing and fast-start escapes away from the stimulus, whereas hatchery-reared fish often ignored or approached the stimulus. Wild fish also had stronger responses, turning faster during escapes and reducing activity immediately after the stimulus. Both fish types were less active on a 'risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…Acoustic cues that could represent threats elicit consistent escape responses in individuals [9], [43], [46] and schools ([37], [47] for summary see [38]). This work represents a positive outcome in that similar to wild cod exposed to acoustic stimuli [48]; the application of infrasound and a surface disturbance event had a short-term effect on salmon behaviours, with fish returning to pre-stimulus states shortly after the cues had ceased. However its effect on flight behaviour may lessen over time as for any stimulus, repeated or extensive exposure can lead to habituation (e.g.…”
Section: Discussionmentioning
confidence: 89%
“…Acoustic cues that could represent threats elicit consistent escape responses in individuals [9], [43], [46] and schools ([37], [47] for summary see [38]). This work represents a positive outcome in that similar to wild cod exposed to acoustic stimuli [48]; the application of infrasound and a surface disturbance event had a short-term effect on salmon behaviours, with fish returning to pre-stimulus states shortly after the cues had ceased. However its effect on flight behaviour may lessen over time as for any stimulus, repeated or extensive exposure can lead to habituation (e.g.…”
Section: Discussionmentioning
confidence: 89%
“…Numerous studies have shown that hatchery reared fish fail to apply appropriate antipredator responses (e.g. Brown & Smith 1998;Nødtvedt et al 1999;Berejikian 1995;Berejikian et al 1999;Meager et al 2011;Benhaïm et al 2012) or they lack cryptic abilities like burying skills and camouflage coloration (e.g. Maynard et al 1996;Fairchild & Howell 2004).…”
Section: Implications Of Domestication For Antipredator Skillsmentioning
confidence: 99%
“…Swimming training is increasing swimming performance (Farrell et al 1990;Anttila et al 2006) and swimming performance is important for foraging, predators defence and for feeding migrations. It has been shown that hatchery rearing reduces flight response behaviour (Meager et al 2011;Benhaïm et al 2012). Meager et al (2011) showed that wild caught Atlantic cod (Gadus morhua) were faster in turning and were turning at larger angles during escapes from a possible predation threat than predator naïve hatchery cod.…”
Section: Enriched Rearingmentioning
confidence: 99%
“…Unlike many areas of the industrialized northern hemisphere, there has not been any seismic survey exploration in this region for many years. At a local scale, construction-related noise from pile driving or dredging makes ephemeral contributions to the ocean soundscape, but these activities are not considered major sound sources in conservation management plans that address acoustic aspects of this region, and navy exercises using tactical sonars are rare [3], [4].…”
Section: Introductionmentioning
confidence: 99%